Ranu Pani Resort Orchid Diversity Atlas - Novita Yanuartanti; Susriyati Mahanal; Murni Saptasari (Jurnal Pendidikan Sains, 2019)
Abstract: This research aims to determine the validity of orchid diversity atlas in the Plant Diversity course for Biology Education students. This research was a development research that referred to ADDIE development model which was limited to the stage of Develop phase. The validity of atlas products was obtained from subject matters expert, media expert and field testing. While for practicality, it can be seen from student responses. The results showed the mean results of the subject matter expert validation score was 97.84%, media validation was 98.75%, field testing was 94%, and student responses was 94%. To sum up, this diversity atlas is valid and practical for plant diversity course. Key Words: orchid diversity atlas, ADDIE development model, plant diversity courseAbstrak: Penelitian ini bertujuan untuk menentukan kevalidan produk atlas keanekaragaman anggrek pada matakuliah Keanekaragaman Tumbuhan untuk mahasiswa Pendidikan Biologi. Jenis penelitian adalah penelitian dan pengembangan yang mennggunakan model pengembangan ADDIE yang dibatasi sampai tahap Develop. Kevalidan produk atlas diuji berdasarkan hasil skor validasi dari ahli materi, media, dan praktisi lapangan, sedangkan untuk kepraktisan dapat diuji dari respon mahasiswa. Hasil penelitian menunjukkan rerata hasil skor validasi materi memiliki nilai persentase 97,84%, validasi media 98,75%, praktisi lapangan 94%, dan respon mahasiswa 94%. Simpulan penelitian adalah produk atlas keanekaragaman anggrek valid dan praktis digunakan mahasiswa dalam matakuliah Keanekara-gaman Tumbuhan.Kata kunci: atlas keanekaragaman anggrek, model pengembangan ADDIE, matakuliah keanekaragaman tumbuhan